Das Erdbeben vom 22. Mai 1960 in der Provinz Llanquihue in Südchile: Bericht eines Augenzeugen - von Bauer, Peter-Paul (ERDKUNDE, 1960)
In the neighbourhood of the Waldhof the following phenomena connected with the earthquakes were noticed: 1. Groundwater oscillation and emersion 2. Formation of crevices and funnels. The Osorno volcano has no permanently flowing surface drainage system. Precipititional and melting waters seep away in the debris (Arenales) at the mountain foot. They flow underground into the River Petrohue. Only when snow melts quickly or after heavy rainfalls the rills (Canjones) carry down the surplus waters on the surface for a short time. After the quakes an important rise of the groundwater was noticed. The low lying land was flooded. Appearantly the waters stored up in the Arenales was pressed to the surface. The groundwater level was presumably put to oscillate. The covering dry layers were soaked, so that streams of wet loarm and sand were pressed up. Areas of up to a hectar of arable land were covered. Fig. 3 shows the crevices and funnels. They are nearly all situated where the mountain foot borders on the swamps. Their orientation is NNE-SSW. Concerning the buildings it could be noticed that solid wood structures on a concrete foundation, and with a nailed wooden shingle-roof, can stand up even against heavy earthquakes. Chimneys should be expediently constructed in one piece and made from concrete material. It is useful to have ones own electricity generator and water supply.